2023
DOI: 10.3390/ma16124205
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Phenomenon of Plasticity Loss of Steel Core Made by Selective Laser Melting Method in Zone of Pressure Mould Conformal Cooling Channel

Abstract: This paper presents the results of testing the mechanical properties of maraging steel 1.2709 that were obtained by the SLM method under uniaxial and triaxial states of stress. The triaxial state of stress was realised by making circumferential notches in the samples with different radii of rounding. The specimens were subjected to two types of heat treatment, which consisted of ageing at 490 °C and 540 °C for 8 h. The results of the tests that were conducted on the samples were considered as references and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Piekło et al [6] analyzed the phenomenon of plasticity loss of steel core with CC. Results showed that the proposed methodology can determine the value of allowable deformations in the cooling channel zone.…”
Section: Introductionmentioning
confidence: 99%
“…Piekło et al [6] analyzed the phenomenon of plasticity loss of steel core with CC. Results showed that the proposed methodology can determine the value of allowable deformations in the cooling channel zone.…”
Section: Introductionmentioning
confidence: 99%